High-throughput, pan-leukocyte biomarkers for the detection of inflammation in human breastmilk and stool - Dunnet, M. J.; Morison, I. M.; Bond, D. M.; Hore, T. A. (Frontiers in Epigenetics and Epigenomics, 2025)
BackgroundDNA methylation can be used to track cellular identity. We have previously developed a high-throughput, cost-effective DNA methylation pipeline containing two loci, HOXA3 and MAP4K1, that can quantify leukocyte proportion amongst a range of background tissues. Here, we apply this pipeline to two clinically relevant tissue samples: breastmilk and stool.ResultsWe report that our leukocyte methylation assay can quantify the proportion of leukocytes in breastmilk, and find leukocyte levels fluctuate dramatically in concert with infection severity. We benchmarked our leukocyte methylation pipeline in stool samples against the commonly used faecal calprotectin assay. Our results show a high concordance between the two methods indicating the viability of our DNA methylation biomarkers in the context of intestinal inflammation.Conclusion:The data presented here emphasise the clinical applicability of our high-throughput DNA methylation assay in the context of mastitis and intestinal inflammation.